Assessment of the Role of Mass Media During COVID-19 and Lockdown in Nigeria. - ODUSOTE, Abiodun Tubosun; IHEANYICHUKWU, Temidayo; TONADE, Adeyinka O. (African Journal of Behavioural and Scale Development Research, 2025)
More than before, Nigerians are confronted with lots of plethora of COVID-19 pandemics. Mass media role has its applied on the people during the lockdown intervention, been used by the governments to restrict the spreads of COVID-19 pandemic among the people. The role of mass media and the impact of lockdown on Nigeria health system over the sudden death are significantly proven and it is vital to everybody to take serious measures to prevent future occurrences of COVID-19 pandemic and other similar diseases that may surface on the geographical land of Nigeria. This study adopted qualitative research by explicitly describing the roles of mass media during the lockdown of COVID-19 pandemic and its collective factors. The venal attitudes of exploiting others through ignorance and the danger of rejecting pharmaceutical drugs over herbal drugs must not be harnessed. This study therefore discovered entrepreneurial opportunities and research development that will be benefitted to Nigeria for further studies.